Studies on Moringa oleifera seeds. 1. The antibiotic compound and its deactivation in aqueous solution - Dayrit, Fabian M (Archīum Ateneo, 1990)
The compounds 4-(alpha-L-rhamnosyloxy) benzyl isothiocyanate (A) and 4-(alpha-L-rhamnosyloxy) phenylacetonitrile (B) were isolated from the raw seeds of ben tree by hot water extraction. A was found to be active against Bacillus subtilis but inactive against Escherichia coli. B was inactive against both organisms. When left to stand in an aqueous methanol solution, A decomposed and lost its antibacterial activity. Authors' summary.